2021
DOI: 10.3390/buildings11070297
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Construction Practices: How to Reinvigorate Vernacular Buildings in the Digital Era?

Abstract: The starting point of this article is the critique on socioeconomic and environmental implications of conventional construction practices around sustainability. The focus is on exploring the sustainability dynamics of the emerging “Design Global, Manufacture Local” (DGML) configuration with emphasis on building construction. Combined with the concept of conviviality which we identify in aspects of vernacular architecture we explore how it can foster meaningful sustainability practices in the construction secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Theoretical frameworks, such as the Open-Source Movement and the Circular Economy Principles, underpin the concept of openness in building construction. In this context, openness refers to transparency regarding the building's life cycle and denotes accessibility to information, knowledge resources, tools, and processes through which a building is designed, built, demolished/disassembled, and assessed in terms of its sustainability [99,100]. Essentially, it involves sharing information about designs, materials, building methods, etc., as digital commons through the internet [101], while design tools and physical production infrastructures, such as factories, makerspaces, and hardware equipment, can also be open-source and shared [58,102].…”
Section: Opennessmentioning
confidence: 99%
“…Theoretical frameworks, such as the Open-Source Movement and the Circular Economy Principles, underpin the concept of openness in building construction. In this context, openness refers to transparency regarding the building's life cycle and denotes accessibility to information, knowledge resources, tools, and processes through which a building is designed, built, demolished/disassembled, and assessed in terms of its sustainability [99,100]. Essentially, it involves sharing information about designs, materials, building methods, etc., as digital commons through the internet [101], while design tools and physical production infrastructures, such as factories, makerspaces, and hardware equipment, can also be open-source and shared [58,102].…”
Section: Opennessmentioning
confidence: 99%
“…One such configuration, codified as "design global, manufacture local" (DGML), has been proposed, building on the distributed production of technologies within the commons framework (Giotitsas et al, 2020;Kostakis et al, 2016). It has been observed that commonsbased communities appropriate technology to create positive feedback loops for degrowth and localised manufacturing and maintenance (Kostakis et al, , 2016 as manifested in numerous fields, including agriculture, building construction, and energy systems (Giotitsas et al, 2022;Priavolou et al, 2021;Troullaki et al, 2022).…”
Section: Design Global -Manufacture Local: a Sustainable Production C...mentioning
confidence: 99%
“…Parallel to the more commercially oriented cases like MakerBot, the same imaginaries were manifested in projects oriented towards social impact. The potential of such configurations has been documented in various domains, such as prosthetics (Kostakis et al, 2018); construction and housing (Priavolou and Niaros, 2019;Priavolou et al, 2021); small-scale wind turbines (Latoufis et al, 2015;Robra et al, 2021); Do Patents Spur Innovation for Society? Lessons from 3D Printing A Pazaitis, C Giotitsas, L Savvides, V Kostakis | mέta Working Paper 7EN2021 33 agricultural machines (Giotitsas 2019;Pantazis and Meyer, 2020;; or emergency response in the context of the COVID-19 pandemic (Pazaitis et al, 2020;Bowser et al, 2021).…”
Section: Towards a Commons-based Innovation Frameworkmentioning
confidence: 99%